Strengthening Devotion - Ramona Rolle-Berg; Kara Vander Linden (Grounded Theory Review: An International Journal, 2020)
The experiences of parents rearing an autistic child(ren) framed an exploration of caregiver well-being using Glaser’s classic grounded theory. The theory delineates struggles, stress, and self-growth through service. Viewed as a roadmap, strengthening devotion guides caregivers through a fear-driven landscape of altered perceptions that fuels evolution in awarenss about what it means to love nonjudgmentally with unqualified faith not only in a child(ren) but in one’s own resilience. Acceptance, adaptation, and a reclaiming of relinguished self-focus define strengthening devotion. In accepting, entrapment wanes as emotions signal reengagement; in adapting, self-esteem develops with emotion regulation; and in reclaiming life, resilience signals reimagining of self. As uncertainty and reactivity are delimited through activities of service, devotion evolves, conceptualized as a stage-dependent growth continuum, namely: Strengthening Parental Devotion, Strengthening Relational Devotion, and Strengthening Personal Devotion. Ultimately, parents may use the strengthening devotion roadmap to corroborate where they have been, how far they have traveled, and chart proactively to lower stress, improve health outcomes and re-engage with life’s unlimited potential.